Two classes of gating current from L-type Ca channels in guinea pig ventricular myocytes (The Rockefeller University Press, 1992)
Intramembrane charge movement was recorded in guinea pig ventricular myocytes at 19-22 degrees C using the whole-cell patch clamp technique. From a holding potential of -110 mV, the dependence of intramembrane charge moved on test voltage (Q(V)) followed the sum of two Boltzmann components. One component had a transition voltage (V) of -48 mV and a total charge (Qmax) of congruent to 3 nC/microF. The other had a V of - 18 mV and a Qmax of 11 nC/microF. Ba2+ currents through Ca channels began to activate at -45 mV and peaked at congruent to -15 mV. Na+ current peaked at -35 to -30 mV. Availability of charge (in pulses from -70 to +10 mV) depended on the voltage of conditioning depolarizations as two Boltzmann terms plus a constant. One term had a V of -88 mV and a Qmax of 2.5 nC/microF; the other had a V of -29 mV and a Qmax of 6.3 nC/microF. From the Q(V) dependence, the voltage dependence of the ionic currents, and the voltage dependence of the availability of charge, the low voltage term of Q(V) and availability was identified as Na gating charge, at a total of 3.5 nC/microF. The remainder, 11 nC/microF, was attributed to Ca channels. After pulses to -40 mV and above, the OFF charge movement had a slow exponentially decaying component. Its time constant had a bell-shaped dependence on OFF voltage peaking at 11 ms near -100 mV. Conditioning depolarizations above -40 mV increased the slow component exponentially with the conditioning duration (tau approximately equal to 480 ms). Its magnitude was reduced as the separation between conditioning and test pulses increased (tau approximately equal to 160 ms). The voltage distribution of the slow component of charge was measured after long (5 s) depolarizations. Its V was -100 mV, a shift of -80 mV from the value in normally polarized cells. This voltage was the same at which the time constant of the slow component peaked. Qmax and the steepness of the voltage distribution were unchanged by depolarization. This indicates that the same molecules that produce the charge movement in normally polarized cells also produce the slow component in depolarized cells. 100 microns D600 increased by 77% the slow charge movement after a 500-ms conditioning pulse. These results demonstrate two classes of charge movement associated with L-type Ca channels, with kinetics and voltage dependence similar to charge 1 and charge 2 of skeletal muscle.(ABSTRACT TRUNCATED AT 400 WORDS)